Method for producing a stable suspension of titanium dioxide heterocrystals and silica particles and stable suspension produced by the method for initiating an active form of oxygen

By using heat treatment and hydrodynamic cavitation homogenizer technology during nanoparticle synthesis, stable titanium dioxide or silica particle suspension is formed, and the stability of nanoparticles at high concentrations and controlled sizes is solved, achieving the realization of the stability of nanoparticles The biological activity and stability of forming reactive oxygen species in organisms are suitable for applications in the medical field.

CN119136816APending Publication Date: 2024-12-13阿卜杜拉・库尔卡耶夫
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280095735.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-03
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to stably synthesize nanoparticles at high concentrations and controlled particle sizes, especially in terms of biocompatibility and bioactivity, which affects their application in the medical field.

Method used

By mixing the starting material with a size greater than 0.5 μm with an aqueous solution of inorganic acid, heat treatment and rotary evaporation, and then adjusting the pulsation wave mode in a hydrodynamic cavitation homogenizer, a stable suspension of titanium dioxide or silica is obtained. Ensure that the particles have up to 80% electron-excited triplet oxygen on the surface of the lattice, forming active form of oxygen, and improving biological activity and stability.

Benefits of technology

Long-term stable activated titanium dioxide or silica particle suspension is achieved, ensuring the formation of active forms of oxygen in organisms, improving its biological activity and physical stability in the medical field, and is suitable for cancer treatment and other medical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136816A_ABST
    Figure CN119136816A_ABST
Patent Text Reader

Abstract

A method of producing a stable suspension of titanium dioxide heterocrystals and silica particles and a stable suspension. The invention relates to a method for preparing an aqueous suspension, comprising mixing a starting material with an aqueous solution of a pharmaceutically acceptable acid followed by a first stage of homogenization for mixing, heat treating the obtained aqueous suspension, directing the aqueous suspension to a rotary evaporator for obtaining activated particles, mixing the activated particles with water in a hydrodynamic cavitation homogenizer, a stable suspension of titanium dioxide heterocrystals or silica particles is obtained, with up to 80% of electronically excited triplet oxygen 3O2 present on the lattice surface at the energy center. The present invention ensures catalytic activity for forming an active form of oxygen in a living organism. The surface of titanium dioxide and silicon dioxide has adsorption capacity, which is an important factor for use in medical forms, ensures detoxification, antiviral and anti-pathogen effects in living organisms, and enhances the induction of immunoreactions in vertebrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of producing stable suspensions of nanometer-sized particles of heterocrystalline minerals and methods for their production.

[0002] Suspensions of titanium dioxide and silicon dioxide nanoparticles are of great interest to industry due to their diverse properties and their potential for use in a wide variety of applications. Background Art

[0003] Preferably, for the preparation of nanoparticles, minerals with heterogeneous crystal structures are used, in particular rutile (TiO2; (Ti, Nb, Fe)O2), anatase (TiO2, (Ti, Nb, Fe)O2), quartzite (SiO2). These minerals are widely distributed in nature and are easy to disperse.

[0004] Rutile is a natural mineral that is the main titanium ore as a source of metal and is used in high-tech alloys due to its low density, high strength and corrosion resistance. Microscopical inclusions of rutile can be found in quartz, tourmaline, ruby ​​and sapphire. During its formation at high temperature and pressure, this stone forms the stable n(SiO2)-n(TiO2) form under these conditions, but when the temperature is lowered and the pressure drops, the two components separate to form rutile crystals that are captured by quartz crystals.

[0005] In particular, due to their physicochemical properties, nanoparticles have become very useful in different fields: treatment of different diseases such as infectious diseases, bacterial or viral infections, cancer treatment, wound healing, anemia treatment, etc.

[0006] WO2007048634 “NANOPARTICLES OF HETEROCRYSTAL FOR USE AS A MEDICAL AGENT AND METHOD OF THEIR OBTAINING”.

[0007] Optimized syntheses performed at low concentrations are difficult to repeat at higher concentrations without stability and aggregation problems, which is why it is important to emphasize that the problem that arises in industrial adaptation is a synthetic system that is stable in time at high concentrations and controlled particle size.

[0008] From the technical field, EP2462915A1 (published on December 24, 2024, with priority to PCT / JP2010 / 062958 on July 30, 2010) is the prior art. "Organic-inorganic composite particles and process for production thereof, dispersion containing the particles, and cosmetic containing the particles" (Organic-inorganic composite particles and process for production thereof, dispersion containing the particles, and cosmetic containing the particles).

[0009] Organic-inorganic composition particles for cosmetics, comprising: inorganic oxide particles, each having a cationic charge on the particle surface; and polymer gel molecules, which are obtained from natural substances and have anionic functional groups and one or more hydroxyl groups in the molecule, wherein the polymer gel molecules are electrostatically bonded to the surface of the inorganic oxide particles. The inorganic oxide particles are particles of oxides or composite oxides of at least one metal element selected from cesium, magnesium, calcium, barium, cerium, titanium, zirconium, vanadium, iron, zinc, aluminum and silicon (excluding silicon oxide particles).

[0010] The average diameter of the organic-inorganic composite particles is preferably in the range of 0.1 to 300 mcm, preferably 0.15 to 280 mcm. Although organic-inorganic composite particles with an average particle diameter of less than 0.1 mcm can be used, the particle dispersion force increases, which complicates the particle handling, and therefore such particles are not ideal. If the average particle diameter exceeds 300 mcm, the spontaneous sedimentation force increases, which makes it difficult to prepare particles uniformly dispersed in the dispersion medium. In the final stage after filtering and drying the organic-inorganic composite particles, water is added for final dispersion.

[0011] For cosmetic purposes, the suspension obtained has uniform flow characteristics.

[0012] From the technical field, European Patent No. 016541 WO2007 / 1188842007.10.25 (PCT PCT / EP2007 / 053761), "Compositions of magnetic nanoparticles and their use" is the prior art.

[0013] The present invention relates to the use of biocompatible nanoparticles or nanoparticle aggregates in combination with an external non-oscillating magnetic field, wherein the nanoparticles comprise: a) a core comprising a magnetic material; b) a biocompatible covering surrounding the core; and, optionally, c) a labeling agent, wherein the outer diameter of the covering is less than about 100 nm, for the preparation of a composition, wherein the composition does not contain any other means for targeting cells. The invention also relates to the composition obtained and its use in the healthcare field for cancer treatment or in diagnostics (e.g., visualization) for monitoring tumor development.

[0014] The ferromagnetic material is selected from the group consisting of iron, nickel, cobalt, gadolinium, samarium, neodymium, boron, aluminum and any mixture thereof. The material of the ferromagnetic core is in the form of oxide, hydroxide or metal.

[0015] The composition may be in solid or liquid form (suspended nanoparticles), for example, in the form of a paste or an aerosol.

[0016] From patent US 2010 / 0262115, a method of obtaining multicomponent particles is known, which comprises a stage of producing inorganic nanoparticles.

[0017] The present invention is directed to a formulation containing nanoparticles for cancer treatment, a pharmaceutical composition containing nanoparticles, and a method of using the same for drug delivery and cancer treatment via ultrasound or light.

[0018] The nanoparticles (encapsulating the contents of hypocrelline-B) containing the contents of hypocrelline-B derivatives and polyvinylpyrrolidone covering are SL052. The nanoparticles are combined with a detected marker. In the nanoparticles, the detected marker is selected from fluorescent or other luminescent markers, radioactive indicators or contrast agents. The nanoparticles are used in combination with one or more pharmaceutically acceptable carriers to form a pharmaceutical composition for tumor treatment.

[0019] Polyvinylpyrrolidone (PVP) (average molecular weight of 40,000 Da) is a derivative of Hypocrellin-B (referred to as "SL052"). SL052-NPS was produced using a sedimentation method. 1.5 ml of a 0.5% (7.5 mg / ml) aqueous solution of PVP was added to 6 ml of water while mixing at room temperature. After 10 minutes, 1.59 ml of 4.6 mM SL052 in dimethyl sulfoxide (DMSO, Fisher Scientific) was added to the mixture. The obtained solution was mixed in the dark for 10 minutes to obtain a nanodispersion with a nanoparticle size of 136 nm.

[0020] The suspensions reported in the literature are either obtained immediately during the synthesis process or by synthesis and deposition of nanopowders followed by redispersion in a solvent in the presence of additives [P K Khanna et al. Mater. Lett., 61 (2007) 3366]; however, it should be noted that in order to promptly improve system stability, to facilitate calibration and to avoid the stages of extraction, washing and repeated dispersion of powders, it is preferred that the nanoparticles are converted into a suspension immediately after synthesis.

[0021] A method for producing a stable suspension of metal nanoparticles Au, Ag, Cu, Pd, Pt, Fe, and a stable suspension of metal nanoparticles Au, Ag, Cu, Pd, Pt, Fe produced in this way, which is carried out in an aqueous medium using a microwave device at low temperature, under pressure and in a heated ambient atmosphere, is known. Application PCT / EP2010 / 052534WO2010 / 100107 (September 10, 2010) is disclosed.

[0022] The term "metal nanoparticles" refers to particles of Au, Ag, Cu, Pd, Pt, Fe with a size ranging from 1 to 250 nm, preferably 1 to 100 nm; in particular, the present invention relates to nanosuspensions of Ag and Au.

[0023] The elaborate process comprises adding a salt water precursor of a metal to a reaction medium heated to reaction temperature and containing a reducing agent, a chelating agent and a catalyst in strictly defined molar ratios of chelating agent / metal, reducing agent / metal and catalyst / metal.

[0024] This method ensures the production of a colloidal suspension that is highly concentrated and stable over a period of time (over a period of greater than 7 months).

[0025] Suspensions produced in this way are characterized by an average dynamic light scattering rate (DLS method) of about 20-30 nm and show a monodisperse distribution before concentration and for higher concentrations a bimodal distribution is observed with a primary particle population present in the 5-10 nm size range.

[0026] The use of suspensions of metal nanoparticles of Au, Ag, Cu, Pd, Pt, Fe is limited due to the unstable suspension conditions and the difficulty in excretion from the human body. In connection with the aggregation of particles, sedimentation occurs and it is not isolated / sampled from the organism.

[0027] Au is chemically inert, does not interact with acids, the aqueous medium of organisms, and oxygen, and is virtually non-isolated / sampled from organisms.

[0028] Studies on the biological properties of silver nanoparticles have shown that in aqueous media, these particles are essentially in the oxide form. In particular, silver oxide has positive biological activities (antibacterial and antitumor) thanks to a photocatalytic mechanism of the passage of dissolved atmospheric oxygen PO2 in the form of active forms of oxygen (AFO).

[0029] Furthermore, silver in suspensions has a tendency to aggregate and lose its oxide form (passages within catalytically inactive quasimetal particles), which toxicologists have a negative view of.

[0030] The technical problem to be solved by the present invention is to obtain stable suspensions (which may be used in medical form compositions) on the basis of crystalline, biodissociable ceramics, i.e. two products of titanium dioxide or silicon dioxide, from which a pronounced biological activity is obtained due to their special structure when obtaining a suspension, the possibility of chemical-physical bonding of the crystal surface with energy reaction centers.

[0031] The technical result is the production of long-term stable suspensions of heterogeneous crystals of titanium dioxide or silicon dioxide with active particles, characterized by the presence of oxygen on their surface, which ensures the production of active forms of oxygen (AFO) in the human body.

[0032] The product representing titanium dioxide heterogeneous crystals is hereinafter referred to as activated titanium dioxide. The particles of activated (nanocrystalline) titanium dioxide still have the crystal structure of pigmentary titanium dioxide in the interior, used as an excipient in pharmaceutical compositions. The improved interphase properties (physical, technical and catalytic properties) due to the activation of the nanoparticles do not lead to the formation of new compounds, but to the same compounds in which the colloidal and surface properties have changed, i.e. the presence of oxygen in the structure, a certain Zeta potential on the crystal surface, ensuring the induction of active forms of oxygen in living organisms.

[0033] The chemical prerequisite for the activation reaction of titanium dioxide heterogeneous crystals or silicon dioxide particles is the chemical adsorption of H + to tune the electrostatic properties of the surface (increase in zeta potential due to increased surface charge density), and to form photocatalytic domains (lattice defects) through corrosive acid treatment of the surface.

[0034] The ratio of particle and crystal charges is one of the factors that determines the physical stability of a suspension.

[0035] By measuring the zeta potential in suspension preparations, the magnitude of the electrostatic repulsion between particles can be quantified, so the higher the zeta potential, the higher the physical stability. Typically, particle charge is defined based on the amount of zeta potential, for example, measured using the electrophoretic mobility of particles in an electric field. Summary of the invention

[0036] Method for producing a stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles, characterized in that a starting material in the form of aggregates with a size greater than 0.5 μm is mixed with an aqueous solution of an inorganic acid, followed by a first stage of homogenization for mixing, then the aqueous suspension obtained is subjected to a heat treatment, then the aqueous suspension is directed to a rotary evaporator operating at a pressure below 100 kPa and at a temperature not higher than 70° C. for evaporating the inorganic acid, wherein the consumption of the suspension by the rotary evaporator is not more than 25 L / min, and then the activated particles obtained are mixed with water in a hydrodynamical cavitational homogenizer in a regulated pulsating wave mode until a stable suspension of titanium dioxide heterogeneous crystals or silicon dioxide particles is obtained, wherein the size of the stable suspension is less than 450 nm and up to 80% of the electron excited triplet oxygen is present on the surface of the lattice at the energy center, i.e. in the quantum dot (QD)-local overheating zone. 3 O2, ensuring catalytic activity for the formation of reactive forms of oxygen (AFO) in living organisms.

[0037] In order to obtain a stable suspension of TiO2 heterogeneous crystals as starting material, a modified TiO2 powder containing anatase and rutile is used, preferably in a ratio of from 10:90 up to 90:10, more preferably from 60:40 up to 40:60.

[0038] The initial starting materials are accordingly mixed with pharmaceutically acceptable hydrochloric acid or sulfuric acid, for example in the form of a 0.0001N-0.1N aqueous solution.

[0039] At the expense of the use of a corrosive acid treatment, the levels of microorganisms, pyrogens and other hydrolyzable organic contaminants are reduced, which is very important for the subsequent elimination of toxicity of the obtained stable suspension and its use in pharmaceutical compositions.

[0040] Pharmaceutically acceptable acids may also be selected from the following acid range: primarily hydrochloric acid, sulfuric acid, as well as metaphosphoric acid, methanesulfonic acid, nitric acid, phosphoric acid, sulfuric acid, tartaric acid.

[0041] In particular, the stability of the suspension obtained is significantly influenced by the pH of the medium obtained as a result of the acid treatment of the starting materials.

[0042] The stability of the obtained suspension is ensured by the low or neutral pH of the suspension medium.

[0043] The mixture obtained is directed to a homogenizer for the primary stage of mixing, for example a device equipped with a supply nozzle interconnected by a jet channel with a coaxial auxiliary chamber, connected thereto by a vortex chamber and a mixing chamber, connected to a discharge nozzle for outputting a homogenous aqueous dispersion after the first stage of mixing.

[0044] Then, the aqueous suspension of titanium dioxide heterogeneous crystals or silicon dioxide particles obtained after homogenization is introduced into an ultrasonic bath with an ultrasonic frequency of 20-90 kHz, where it is maintained at a temperature not higher than 70° C. for not more than 2 hours.

[0045] In a vacuum rotary evaporator, the dispersion medium is evaporated at a pressure of less than 100 kPa and a temperature not higher than 70° C. for evaporating a pharmaceutically acceptable acid wherein the consumption of the suspension by the rotary evaporator is not greater than 25 L / min.

[0046] During the evaporation of the dispersion medium, volatile acid vapor is released. At this time, the surface of the particles and crystals is activated. After the activation, the TiO2 or SiO2 powder is obtained, and the crystals and particles have a developed surface and a special structure.

[0047] The triplet condition in the third stage of metastable electron excitation 3 Activated crystalline TiO2 or granular SiO2 is obtained in O2, in which the presence of oxygen in the structure is as high as 80%. Under this condition, the TiO2 particles have a Zeta potential of +30 to +15 mV, the SiO2 particles have a Zeta potential of -20 to -15 mV, and the TiO2 crystals or SiO2 particles are characterized by the presence of adsorption properties.

[0048] Zeta potential was measured with the aid of a Malvern ZetasizerNano ZS instrument (Phase Analysis Light Scattering). The zeta potential range is 10-100 mV.

[0049] The powder of activated TiO2 or SiO2 particles is directed in a hydrodynamic cavitation homogenizer, wherein water is added to obtain a stable suspension of 0.0001%-10% TiO2 heterogeneous crystals or SiO2 particles.

[0050] The treatment process in the hydrodynamic cavitation homogenizer lasts about 10 minutes, depending on the desired specified index of suspension.

[0051] The homogenizer comprises: fluid medium processing modules, which are sequentially connected to each other along the flow of the mixed medium, wherein the first pre-mixing module comprises an inlet nozzle for the base medium, an inlet nozzle for the mixed medium and an outlet channel for the mixed medium, the last of which overflows into a homogenization block through which it overflows and then overflows into a controlled output module of the homogenized product, wherein, according to the present invention, in the homogenization module, a cavitation mixing chamber is formed at the output end of the chamber by a reflector for flow mixing, which is arranged in the form of narrowing along the wall of the flow chamber, wherein in the chamber, an insert with a central channel is installed, a spiral groove is provided on the outer surface of the insert, the insert is in contact with the inner wall of the chamber, an open-ended spiral channel can be formed along the spiral groove and the flows of the spiral channel and the central channel are mixed in the cavitation chamber before the reflector, the central channel is provided with a narrowing portion and a widening portion, wherein the controlled output module is provided with a control rod of the flow medium reflector, the protrusion of which is located at the homogenizing module (homogenizing block) The control rod is arranged in a communication passage of an outlet of a block, and the control rod is connected to a device for changing the position of its protrusion in the communication passage.

[0052] In the cavitation chamber, an insert with a central channel is installed, and a spiral groove is provided on the outer surface of the insert. The insert contacts the inner wall of the chamber, and an open-end spiral channel can be formed along the spiral groove and the fluids in the spiral channel and the central channel are mixed in the cavitation chamber before the reflector.

[0053] The fluid product fed into the chamber twists in the spiral channel formed by the spiral groove to form a pulsating strong vortex layer.

[0054] In the homogenization chamber, a strong vortex layer is formed on the flow surface, which, on account of the thermophysical effects of the impact, excites turbulent wave pulsations when hitting the reflector, wherein the temperature of the treated fluid medium / product increases.

[0055] The structure of the cavitation homogenizer ensures a high degree of homogenization of the suspension obtained.

[0056] The suspension stability depends on the existence of process procedures and operations, the use of starting materials (i.e., the combination of anatase and rutile in obtaining a titanium dioxide heterogeneous crystalline suspension), the use of acid solutions, different types of homogenizers during the mixing first stage and the use of a hydrodynamic cavitation homogenizer for the final mixing and obtaining a stable suspension.

[0057] The stable suspension of titanium dioxide crystals and silicon dioxide particles obtained according to the well-designed method is characterized by a distribution of activated titanium dioxide crystals with a size of 0.3 vol% of particles up to 1 nm, 5-40 vol% of particles up to 20 nm, 10-80 vol% of particles up to 80 nm, 5-30 vol% of particles up to 150 nm, 5-20 vol% of particles up to 250 nm, and no more than 10 vol% of particles larger than 250 nm, and a distribution of activated silicon dioxide particles with a size of 10-80 vol% of particles 40-80 nm, 10-80 vol% of particles 80-150 nm, less than 30 vol% of particles 150-250 nm, and no more than 15 vol% of particles larger than 250 nm, based on the results of a photon correlation spectroscopy instrument Malvern ZetasizerNano. The data obtained by ZS analysis are characterized by the presence of up to 80% of electronically excited triplet oxygen at the lattice surface in the energy centers, i.e., in the quantum dot (QD)-local overheated regions. 3 O2, ensuring catalytic activity for the formation of reactive forms of oxygen in living organisms. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 Showing the volume distribution of titanium dioxide particles of different sizes in the suspension.

[0059] Figure 2 Showing the volume distribution of silica particles of different sizes in the suspension. DETAILED DESCRIPTION

[0060] The polydispersity of the suspensions obtained determines their unique properties when forming a medicament, which ensures not only targeted delivery to the area of ​​the pathological process but also a unique mechanism of action used in the medicament.

[0061] The obtained polydisperse suspension is bioactive not only due to the photocatalytic properties but also due to thermal activation, which is achieved for the first time at the expense of the human body temperature of 36.6 °C.

[0062] In the case of a regulated modulated change of the electrostatic properties achieved due to lattice defects of the extended crystal surface, the crystals, depending on the size and structure of the surface and the corresponding charge (zeta potential), gain the possibility of acting as photocatalysts in a wide wavelength range from ultraviolet to infrared irradiation.

[0063] Another advantage of using heterogeneous crystals and particles as photocatalysts is that they can be activated with the aid of visible light.

[0064] Another advantage is that in one therapeutic dose the ratio of crystals and particles of different sizes can be adjusted in photodynamic therapy (PDT), not only depending on the nature of the effect on the pathology.

[0065] The suspension obtained by the well-designed method has a time stability of 24 months to not less than 15 years. In the stability test, the optical properties (spectrum in the UV-visible range, Figure 3 , Figure 4 No changes were observed in the particle size (DLS), indicating that the number and size of the particles did not change over time.

[0066] The stability test of QD series suspension ADAM QD / T (TiO2) is shown below.

[0067] Tables 1 and 2 show the results obtained during conventional (long-term) stability studies (+25±1° C.).

[0068]

[0069]

[0070] The data obtained show that:

[0071] The pH of these samples showed no obvious trend change.

[0072] The dynamic viscosity of these samples did not change significantly during storage.

[0073] The colloidal stability of the product was found to be excellent and no tendency of change in the particle size of the product was found.

[0074] The titanium dioxide content of the product did not change during storage.

[0075] Sterility and endotoxin content investigations were only specified at the end of the storage study. These samples were found to be sterile and to contain endotoxins below the specified concentration.

[0076] In accelerated and long-term stability testing, the appearance of samples stored under different storage conditions showed no changes that were different from the specifications.

[0077] Tables 3 and 4 show the results obtained during a routine (long-term) stability study (QD)ADAMQD / S(SiO2), t = +25±1°C.

[0078]

[0079]

[0080] The data obtained show that:

[0081] The pH of these samples showed no obvious trend change.

[0082] The dynamic viscosity of these samples did not change significantly during storage.

[0083] The colloidal stability of the product was found to be excellent and no tendency of change in the particle size of the product was found.

[0084] The silica content of the product did not change during storage.

[0085] Sterility and endotoxin content investigations are only scheduled to be performed at the end of the planned period of the storage study and are found to meet product specifications.

[0086] In accelerated and long-term stability testing, the appearance of samples stored under different storage conditions showed no changes that were different from the specifications.

[0087] Thus, due to the combination of carefully designed procedures and operations of the method, in particular due to the use of different special homogenizers during the processing stages, continuous stability of the suspension is ensured.

[0088] The presence of oxygen O2 (occupying up to 80% of the structure) on the crystal surface and the presence of a large number of ligand ionic groups at the breaks in the unfolded surface of the crystal lattice ensure the formation of exciton structures, ionic bonds and local energy superheated zones (i.e. quantum dots), where O2 is in a metastable electronically excited triplet state condition ( 2 T 3+ ), has a unique feature of conversion into biological activity - singlet state condition (S -1-3 ).

[0089] Measurement of electronically excited triplet oxygen ( 2 T 3+ ) Pharmacological studies were performed as follows. The study was conducted on one male rabbit (without lesions) weighing 0.75 kg.

[0090] 5 ml of suspension were injected through the needle, where 5 ml of injection water and 3 mg of TiO2, at the entrance inside the needle opening there was a light guide for supplying laser photons and simultaneously supplying the injection suspension.

[0091] The photothermal procedure was performed using an IR960nm laser with 3Wt power and 20J synchronously regulated dose.

[0092] A sensor for measuring O2 was installed at the local treatment site of the rabbits with the aid of an additional needle, and singlet oxygen was analyzed by an automatic chemiluminescent gas analyzer (model FOMS-200OXYGEN, manufactured by FRG, Federal Republic of Germany). 3 O2.

[0093] Repair of the presence of up to 80% triplet oxygen in the oxygen structure under metastable electronic excitation conditions to singlet conditions (S -1-3 ) conversion.

[0094] The surfaces of titanium dioxide heterogeneous crystals and silicon dioxide particles have adsorption capacity, which is an important factor for use in medical forms.

[0095] The reactive chemical groups at the locations where the crystal lattice is broken easily form chemical bonds with the same reactive molecules in the environment.

[0096] The existing mechanisms of adsorption interactions between molecules of different substances are:

[0097] Non-specific binding to porous structures;

[0098] Ion adsorption;

[0099] · Covalent bond.

[0100] Since the surface of titanium dioxide crystals and silicon dioxide particles contains up to 80% oxygen and there are a large number of ionic groups of ligands at the breaks of the unfolded lattice surface, forming an exciton structure, ionic bonds and a series of local energy overheating zones are ensured, all types of adsorption are possible, which determines the detoxification possibility of the obtained stable suspension.

[0101] Studies have shown that in a dose of 1 mg / ml formulation containing a stable suspension of titanium dioxide crystals or silicon dioxide particles, the adsorption capacity is twice as high as that of existing formulations due to the adsorption properties of the crystals and particles.

[0102] Figure 5 The comparative data of adsorption efficiency of exogenous creatinine in the experiment are shown.

[0103] The experiment was conducted on a rabbit weighing 3 kg. The adsorption capacity of 10 g sample of activated carbon was studied, with arteriovenous infusion of 50 ml / min-20 min, and TiO2I 0.6 mg in 1 ml aqueous suspension, injected intramuscularly, at the level of creatinine adsorption. The tests were conducted under the same lighting conditions. Figure 5 On the image:

[0104] 1-Before use (mg %).

[0105] a - not used,

[0106] b-activated carbon sample,

[0107] Stable suspension of c-TiO2 or SiO2.

[0108] 2-After injection;

[0109] 3-1 hour later;

[0110] After 4-3 hours.

[0111] From the experimental data it can be concluded that the adsorption capacity of the obtained stable suspension of titanium dioxide and silicon dioxide in pharmaceutical form will ensure detoxification by the organism.

[0112] Every neutral inorganic object found in living tissue inevitably belongs to the category of "foreign matter", that is, associated with formations with predominantly pathological characteristics.

[0113] Biocompatible TiO2 crystals and SiO2 particles are the only ones that are of minimal importance for use in different forms of pharmaceutical preparations.

[0114] The results of toxicology studies confirmed the absence of general and local toxicity.

[0115] No side effects were revealed in toxicity tests and repeated administration tests, and the results also confirmed the absence of mutagenicity and teratogenicity. The parenteral tolerance dose for TiO2 is 21.72 mg / kg bw, and the parenteral tolerance dose for SiO2 is 11.39 mg / kg bw. The oral tolerance dose for TiO2 is 2172 mg / kg bw, and the oral tolerance dose for SiO2 is 1139 mg / kg bw (File No.: 488.729.2117; 488.729.2119, from July 6, 2010, TOXI COOP Zrt).

[0116] For example, metal (especially Fe) compounds automatically enter the restricted area for use in pharmacy and obtaining pharmaceutical receipts for preparations. Metals of Fe belong to the "heavy" group and are considered "xenobiotics" and are not released from living organisms.

[0117] An exception is the group of precious metals. But in fact, only silver is considered in this group.

[0118] Examination of the biological properties of silver nanoparticles shows that in aqueous media (such as biological tissues), these particles are essentially in the oxide form. Silver oxide has positive biological activities (antibacterial, antitumor), in particular, due to the photocatalytic mechanism of the conversion of dissolved atmospheric oxygen (PO2) into active forms of oxygen (AFO). However, silver has many drawbacks: aggregation in suspensions, loss of the oxide form (conversion into catalytically inactive particles of metalloids).

[0119] The biological inertness of TiO2 crystals and SiO2 particles is well known, and they acquire the ability to express and regulate biological activity during their specific production methods, as a result of which local energy superheating zones appear (dela Hoz A, Diaz-Ortiz A, Moreno A. Microwaves in organic synthesis. Thermal and non-thermalmicrowave effects. Chem Soc Rev. 2005 Feb; 34(2): 164-78. doi: 10.1039 / b411438h. Epub 2005Jan 12. PMID: 15672180), ensuring catalytic activity for the formation of active forms of oxygen in living organisms.

[0120] The catalytic properties of the crystals and particles are unique in the field of producing different forms of agents to affect a variety of pathogens.

[0121] Under normal conditions, atmospheric oxygen is in principle 1 O2 conditions, such a molecule cannot participate in oxidative biological processes because its activation is heterogeneous, with an energetically excited "triplet-singlet" transition 3 TO2→ 1 SO2 must occur, i.e. the process can only be triggered at the expense of the catalytic properties of crystals and particles (TiO2, SiO2) by transferring an additional energy of 130-180 kJ / mol, i.e. at the expense of an endothermic reaction with enthalpy (Janbazi H, Schulz C, Wlokas I, Peukert S. Thermochemistry of Oxygen-Containing Organosilane Radicals and Uncertainty Estimations of Organosilane Group-Additivity Values. J Phys Chem A. 2021 Oct 7; 125(39): 8699-8711. doi: 10.1021 / acs.jpca.1c06941. Epub 2021 Sep 24. PMID: 34559967).

[0122] Obtaining active singlet oxygen is much easier to achieve in a gaseous medium, for example, by direct absorption of photons. In a fluid medium, this transformation is not possible. In addition, specific catalysts - photocatalysts - (photosensitive PS) are required in the form of TiO2 and SiO2 (QD) crystals and particles.

[0123] change 3 TO2→ 1 SO2 conditions:

[0124] The photosensitive PS must be in heterogeneous conditions (polymer, suspension) and for the “triplet-singlet” transition 3 TO2→ 1 SO2, which must have additional energy (E) from the outside, is not less than 130-180 kJ / mol.

[0125] The photocatalyst, the photosensitive PS, must have oxygen molecules in an electronically excited form.

[0126] In solution, the catalytic reaction can only be carried out by contact with the photocatalyst - a photosensitive PS containing TiO2 and SiO2 (QD) crystals and particles.

[0127] On the surface of heterogeneous crystals and particles, there must be energy centers (local overheating zones) where oxygen molecules are in the triplet state;

[0128] At the zone contact, the energy is sufficient for 3 TO2→ 1 SO2 conversion;

[0129] Catalysis is heat-dependent: temperature rises and the 3 TO2→ 1 SO2 conversion process.

[0130] The reaction in the present invention is achieved for the first time by the energy of the human body's own environment at 36.6°C, and in the case of specific diseases (pathologies), when photon thermal therapy is required, the use of electromagnetic wave emitters can also achieve complex therapeutic effects.

[0131] The mediator in a liquid, aqueous medium, ie in a biological tissue, can be a dense, insoluble substance having a maximum developed surface on which there are a sufficient number of active energy centers, such as TiO2 and SiO2 crystals and particles.

[0132] Another advantage of using heterogeneous crystals and particles as photocatalysts is that they can be activated under a wide range of irradiation, from ultraviolet to infrared.

[0133] Table 5 shows comparative data of sensitizing materials and TiO2, SiO2 (QD) crystals and particles.

[0134]

[0135] The table shows that TiO2 and SiO2 crystals and particles have fundamental advantages over sensitizing substances (photocatalysts) pigments:

[0136] No general toxicity;

[0137] ·Colorless, transparent, inherent optical density;

[0138] Insolubility (forming a heterogeneous suspension structure);

[0139] Large contact area with the medium;

[0140] There are active energy centers (local overheating areas) on it;

[0141] High thermal stability - prevents damage caused by laser impact;

[0142] The catalytic activity is greatest in low optical density areas of the tissue;

[0143] Wide range of spectral photosensitivity;

[0144] AFO synthesis can be achieved by thermal activation at a temperature of 36.6°C.

[0145] The action of the suspension based on the titanium dioxide crystals and silicon dioxide particles is intended to stimulate natural processes at the cellular level. When used in a medical form, the AFO synthesized from QD crystals or particles initiates the process of affecting the cells in question.

[0146] Due to the synthesis of regulated reactive oxygen species AFO, a stable suspension of titanium dioxide crystals or silicon dioxide particles is first directed selectively to the problematic cells of the organism, targeting areas of inflammation both infectious and non-infectious and, in particular, interacting with the membrane-associated enzyme NADF-H (immune cells of phagocytes and macrophages), causing them to undergo numerous cell morphological changes (vacuoles in the cytoplasm, membrane fragmentation, mitotic abnormalities), thus triggering apoptotic or necrotic type death of pathogenic cells (since pathogenic cells do not have effective antioxidant enzymes).

[0147] Many studies have shown that all cells that form the vascular lining produce AFOs in large quantities as a response to physical stimuli (e.g. to pulsatile blood flow) and to hormonal factors (particularly angiotensin). In this model, the consequences of the intensification of AFO production caused by regulatory factors were studied in detail.

[0148] Hishikawa K., Oemar BS, Yang Z., Luscher TF (1997). "Pulsatile Stretch Stimulates Superoxide Production and Activates Nuclear Factor-kappa B in Human Coronary Smooth Muscle." Circulation Research, 81, 797-803.

[0149] Krieger-Brauer HI, Medda PK, Sattel B., Kather H. (2000). "Inhibitory effect of isoproterenol on NADPH-dependent O2 generation in human adipocyte plasma membranes is mediated by betagamma-subunits derived from G(s)." J Biol Chem, 275(4), 2486-90.

[0150] The targeted action of penetrating problematic cells of the organism and reaching infectious and non-infectious inflammatory areas is conditioned by the doubling of the oxygen demand in the inflammatory lesions.

[0151] Example of targeted delivery of stable dispersions.

[0152] Figure 6 An example of studying the penetration of a stable dispersion of titanium dioxide crystals and silica particles labeled with rhodamine into luminescent cells is shown. Fluorescent QDs are taken up by tumor cells of mouse fibroblasts (NIH-3T3). From top to bottom, left to right, over time: Confocal laser fluorescence microscopy images showing QD uptake by the tumor and then the QD crystals moving away from the cells.

[0153] Studies using confocal laser microscopy have shown that luminescent crystals of the QD series, labeled with rhodamine, penetrate into the interior of the cell. The crystals initially accumulate in the cytoplasm. The nucleus accepts the crystals to a lesser extent. In the upper left part of the combined picture, a normal transmission microscopic image of a treated cell can be seen, with visible (dark black) crystals inside the cytoplasm. Microscope images were recorded sequentially, with the treated cells cut into 1 μm thick layers. Remarkably, the cutting of the apical basal part of the cell showed that many luminescent crystals fell off until they were completely removed.

[0154] Example

[0155] Example of producing stable suspension TiO2

[0156] Example 1

[0157] The initial powder of nano-titanium dioxide in the form of aggregates with a size of 0.5 μm (modification of anatase and rutile in a ratio of 10:90) was a white powder with a characteristic odor of butanol and isobutanol (eobutanol).

[0158] Preparation of solutions 500 ml of 0.1 N initial HCl solution was prepared from aqueous HCl.

[0159] dispersion.

[0160] Weigh 100.0 g of moist TiO2 (recalculate dry mass). Dispersion of TiO2 is performed in 300 ml of 0.1 N HCl solution.

[0161] The irradiation method is an ultrasonic bath.

[0162] For the preparation, the suspension was irradiated in an ultrasonic bath operating at a frequency of 20-90 kHz (bath temperature: 60° C., irradiation time: 10-90 minutes).

[0163] Evaporation of the dispersion medium.

[0164] The dispersion medium was evaporated in a vacuum rotary evaporator.

[0165] During the evaporation of the dispersion medium, the volatile vapor of hydrochloric acid is finally discharged.

[0166] filter.

[0167] Filter the dispersed suspension through filter cloth. IPC 2: Ensure filter integrity.

[0168] Evaporation of the dispersion medium.

[0169] In a vacuum rotary evaporator, the dispersion medium is evaporated at a pressure of less than 100 kPa and a temperature not higher than 70 ° C. During the evaporation of the low-pH dispersion medium, the volatile vapor of hydrochloric acid is discharged. At the same time, the surface of the nanoparticle TiO2 is activated, which is due to the significant change in the chemical properties on the surface. After the dispersion medium is evaporated, a dry activated powder TiO2 is obtained.

[0170] The powder of activated particulate TiO2 is directed to a hydrodynamic cavitation homogenizer, where water is added to obtain a 0.001%-10% TiO2 stable suspension and exposed to additional treatments during 10-90 minutes.

[0171] The suspension obtained in this way has a temporal stability of at least 24 months. The optical properties show no change over a period of not less than 15 years.

[0172] Example 2

[0173] The initial powder of nano titanium dioxide (modification of anatase and rutile in a ratio of 10:90) was a white powder in the form of aggregates with a size of 0.5 μm, having a characteristic odor of butanol and isobutanol.

[0174] Solution Preparation - Prepare 500 ml of 0.1 N initial HCl solution from aqueous HCl.

[0175] dispersion.

[0176] Weigh 100.0 g of TiO2 (recalculate dry mass). Disperse TiO2 in 300 ml of 0.1 N HCl solution.

[0177] The irradiation method is an ultrasonic bath.

[0178] For the preparation, the suspension was irradiated in an ultrasonic bath operating at a frequency of 20-90 kHz (bath temperature: 60° C., irradiation time: 1.2 h).

[0179] Filtration. Filter the dispersed suspension through filter cloth. IPC 2: Ensure filter integrity.

[0180] Evaporation of the dispersion medium.

[0181] In a vacuum rotary evaporator, the dispersion medium is evaporated at a pressure of less than 100 kPa and a temperature not higher than 70°C. During the evaporation of the pH dispersion medium, the volatile vapor of hydrochloric acid is discharged. At the same time, the surface of the TiO2 nanoparticles is activated, which is due to the significant change in the chemical properties on the surface. After the dispersion medium is evaporated, a dry activated powder TiO2 is obtained.

[0182] The powder of activated particulate TiO2 is directed to a hydrodynamic cavitation homogenizer, where water is added to obtain a 0.01%-10% TiO2 stable suspension and exposed to additional treatment during 10-90 minutes (1 minute for 10 L of treated suspension, where the content depends on the specified indicator, i.e. 0.001-10%).

[0183] The suspension obtained in this way has a temporal stability of at least 24 months. The optical properties show no change over a period of not less than 15 years.

[0184] Example of producing a stable SiO2 suspension

[0185] Example 3

[0186] 255 g of initial silica nanopowder was dispersed in 10 L of water, and 0.0001 N HCl solution was added. Then, the dissolved nanopowder was placed in a reaction vessel with a volume of 5000 ml, where it was dispersed at a speed of 101 / min under a pressure of 900 kPa-1200 kPa.

[0187] The irradiation method is an ultrasonic bath.

[0188] For the preparation, the suspension was irradiated in an ultrasonic bath operating at a frequency of 20-90 kHz (bath temperature: 60° C., irradiation time: 1.2 h).

[0189] A suspension of SiO2 nanoparticles was obtained with a particle size of 95.0% by number <250 nm and a silicon dioxide content of 50 mg / ml.

[0190] The reaction mixture was filtered through a 10 μm mesh filter (Sefar Medifab).

[0191] After filtration, the entire volume of the suspension was pumped into a glass container and stoppered thoroughly.

[0192] The obtained suspension was placed in an autoclave at a temperature of 121° C., exposure time: 30 minutes.

[0193] Evaporation of the dispersion medium.

[0194] The dispersion medium was evaporated in a vacuum rotary evaporator at a pressure of less than 10 kPa and at a temperature not higher than 70°C.

[0195] During the evaporation of the low pH dispersion medium, the volatile vapors of hydrochloric acid are discharged. At the same time, the surface of the SiO2 nanoparticles is activated, because the chemical properties on the surface change significantly. After the dispersion medium is evaporated, dry activated powder SiO2 is obtained.

[0196] The mixed aqueous mixture of silica was circulated through a suspension device in a hydrodynamic cavitation homogenizer with an input pressure of 900 kPa-1200 kPa (supplied by SCHALI / Prommet / SA) at room temperature for up to 90 minutes.

[0197] Appearance - White or off-white suspension, becomes transparent orange after shaking, and is easy to resuspend.

[0198] Particle size (EP 2.9.31): minimum 90.0% by number <250 nm. Silicon dioxide content: 50 mg / ml, product pH: 5.0-7.5, dynamic viscosity: 0.94-1.14 mPa·s.

[0199] The time stability of the suspension obtained in this way is at least 24 months. No changes in optical properties are shown over a period of not less than 15 years. The present invention relates to a stable suspension of titanium dioxide or silicon dioxide heterogeneous crystals, a method for producing the nanosuspension, and the use of the nanosuspension, which ensure more effective delivery of bioactive agents in the bloodstream of a subject. When such a nanosuspension contacts a body organ (e.g., the oral region, including the cheek mucosa), the compound is absorbed into the bloodstream in an amount sufficient to cause a specific biological response. Accordingly, the nanosuspension suspension can be delivered by means of commonly used microfluidized sprays, hydrogels, topical products, aerosols, or liquids. Delivery can be performed by parenteral, intrathecal, intravenous, through mucosal or all other generally recognized drug delivery methods.

[0200] Thus, stable suspensions of titanium dioxide hetero-crystals and silicon dioxide particles obtained according to a well-designed process for use in medicaments are claimed for intravenously, intramuscularly, orally, nasally, vaginally, rectally, topically and locally (ENT).

[0201] The crystals are characterized by the fact that on the surface the acceptor, i.e. O2, is initially in an excited triplet state and the catalytic potential in AFO is regulated, which is sufficient for use in medical form even at human body temperature of 36.6°C.

[0202] Titanium dioxide heterocrystals or silicon dioxide particles are characterized by the presence of oxygen crystals O2 on the surface, which occupy up to 80% of the structure and are biologically active not only due to photocatalytic properties but also due to the thermotherapy principle, which was achieved for the first time at human body temperature of 36.6°C.

[0203] At the expense of synthetic reactive oxygen species modulating AFO, the medical modalities based on titanium dioxide or silicon dioxide crystals first selectively penetrate into the pathogenic cells of the organism, localizing areas of inflammation both infectious and non-infectious, in particular, cells, phagocytes and macrophages that use fermentation NADF-H to form AFO, which causes a number of cell morphological changes (vacuoles in the cytoplasm, membrane ruptures, mitotic abnormalities), which trigger apoptotic or necrotic type death of pathogenic cells (since pathogenic cells do not have effective antioxidant enzymes). The reactive oxygen species modulating AFO first attracted attention in pathologies in focus (respiratory burst), where the oxygen demand increases many times. Neutrophils (immune cells, leukocytes) take up microorganisms using the NADF-H oxidase membrane-bound enzyme complex, which can be reversed into the extracellular space of the plasma membrane and also into the membrane of the phagosome.

[0204] NADF-G oxidase (NOX) is one of the major sources of reactive form of oxygen (AFO) for cells and is formed by catalysis.

[0205] The stable suspension of titanium dioxide crystals and silicon dioxide particles ensures the induction of an immune response in vertebrates by means of physical or chemical interaction with the antigen.

[0206] Photocatalytic properties of titanium dioxide or silicon dioxide heterocrystals - mobilization in the human or animal body for normalization of the immune response to pathogens and AFO preparation.

[0207] Laboratory and clinical studies show that when the oxygen O2 on the lattice is initially in an excited state 2 T 3 When using a crystal sensitizer in a pharmaceutical hydrogel composition (use form: topical, nasal, throat, mucous membrane, vaginal, rectal, oral), as well as a medical product for topical use in the form of a hydrocolloid medical plaster, for impregnation of tampons, absorbent pads, diapers, tapes, bandages, etc., it has antibacterial and antiseptic effects, anti-inflammatory effects, immunomodulatory effects and adsorption effects, depending on its use form and method.

[0208] The mechanism of action in the composition of the medical product or gel is the interaction of electronically excited O2 on the surface of the formed crystals or particles with the membrane cell enzyme complex NADF-H AFO.

[0209] The efficiency of using a stable suspension of TiO2 heterogeneous crystals and SiO2 particles for adjuvant therapy of cancer diseases has also been demonstrated in combination with cytostatics (doxorubicin, lenalidomide (Revlimid), nivolumab (Nivolumab), ibrutinib (Ibrutinib)).

[0210] Positive results were shown in the model with metastasis to the spleen and liver, with significant reduction in primary tumor size after intraperitoneal administration of the cytostatic agent. In addition, a trend towards a reduction in metastatic lymph nodes was observed.

[0211] Experiments have shown that stable suspensions of titanium dioxide heterogeneous crystals or silicon dioxide particles can be used to formulate medicaments for intravenous, intramuscular, oral, nasal, vaginal, rectal, topical (ENT) or local administration, wherein the amount of therapeutically important active substance is from 0.006 mg / ml for intravenous use, from 0.01 mg / ml for intramuscular use, from 0.01 mg / ml for oral use, from 0.01 mg / ml for nasal use, from 0.01 mg / ml for vaginal use, from 0.01 mg / ml for rectal use, from 0.01 mg / ml for topical ENT use, from 0.001 mg / ml for ophthalmic use, and from 0.0003 mg / g for topical use of medical products in the form of hydrocolloid medical plasters.

[0212] The stable amount contained in the medical form is selected according to known principles of pharmacy, clinical medicine and pharmacology. Generally, it refers to the therapeutically effective amount of the medical treatment. The term "therapeutically effective amount" refers to the pharmaceutically effective amount considered with respect to, for example, a pharmaceutical formulation. The pharmaceutically effective amount is the amount of a pharmaceutical therapeutic agent or a pharmaceutically active substance that is sufficient to achieve an acceptable biological response in its use.

[0213] Medication is available in the form of rectal vaginal suppositories, gels, ointments, or liquids.

[0214] Industrial Applicability

[0215] A well-prepared stable suspension for use in a pharmaceutical composition has the following advantages:

[0216] It is a catalyst for energy exchange reactions;

[0217] No general toxicity;

[0218] ·No allergenicity, i.e. hypoallergenic;

[0219] No harmful toxicological compounds;

[0220] ·The heterogeneous suspended structure is a photocatalyst with catalytic properties;

[0221] · Possesses anti-pathogenic and anti-viral activity, preventing viral penetration into cells and promoting viral destruction due to damage to lipid membranes.

[0222] Can effectively affect pathogens.

[0223] ·High light capacity (5Wt / sq.cm or more) can be used.

[0224] The influencing process can be accelerated (up to 1-3 minutes).

[0225] The photocatalysts did not produce toxic effects, regardless of whether photodynamic therapy (PDT) was performed;

[0226] The use of stable suspensions obtained by a carefully designed process ensures antiviral therapeutic effect, antipathogenic therapeutic effect, the adsorption capacity of crystals and particles ensures detoxification of organisms, ensures elimination of insufficient oxidative processes in living organisms.

[0227] Application of suspensions in modern medical pharmacy

[0228]

Claims

1. A method for producing a stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles, characterized in that: The starting material in the form of aggregates with a size greater than 0.5 μm is mixed with an aqueous solution of a pharmaceutically acceptable acid, followed by homogenization for the first stage of mixing, and then the obtained aqueous suspension is subjected to a heat treatment, and then the aqueous suspension is directed to a rotary evaporator operating at a pressure below 100 kPa and a temperature not higher than 70° C. for evaporating the pharmaceutically acceptable acid, wherein the consumption of the suspension by the rotary evaporator is not more than 25 L / min, and then the obtained activated particles are mixed with water in a hydrodynamic cavitation homogenizer in a regulated pulsating wave mode until a stable suspension of titanium dioxide heterocrystals or silicon dioxide particles is obtained, wherein the size of the stable suspension is less than 450 nm and at the energy center, i.e., in the quantum dot (QD)-local overheating zone, there is up to 80% of electronically excited triplet oxygen 3O2 on the lattice surface, ensuring catalytic activity for the formation of active forms of oxygen in living organisms.

2. The method for producing a stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claim 1, characterized in that The obtained aqueous suspension of titanium dioxide heterogeneous crystals or silicon dioxide particles is directed to an ultrasonic bath having an ultrasonic frequency of 20-90 kHz for heat treatment, and the aqueous suspension is maintained at a temperature not higher than 70° C. for not more than 2 hours.

3. The method for producing a stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claim 1, characterized in that: The activated particulate TiO2 or SiO2 obtained is mixed with water in a hydrodynamic cavitation homogenizer in a regulated pulsating wave mode until a stable suspension of titanium dioxide heterogeneous crystals or silicon dioxide particles having a concentration of 0.0001-10% by mass in the suspended state is obtained.

4. The method for producing a stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claims 1-3, characterized in that In the hydrodynamic cavitation homogenizer, the mixed medium flow passes through a first module for preliminary mixing, and further passes through a module for cavitation homogenization, and then passes through a module that can adjust the dosage of the ingredient flow, and is then guided into a module where the output of the homogenized product after pulsating wave homogenization is regulated, wherein the pulsating chamber of the wave mixing is performed by a regulating reflector of the mixed flow installed at the output of the chamber.

5. The method for producing a stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claims 1-4, characterized in that Under metastable electron excited triplet conditions 3O2, in the presence of up to 80% oxygen in the structure, activated titanium dioxide crystals or silicon dioxide particles are obtained, wherein the titanium dioxide particles have a Zeta potential of +30 to +15 mV, the silicon dioxide particles have a Zeta potential of -20 to -15 mV, and are characterized by the presence of adsorption properties.

6. A stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles produced according to claim 1, characterized in that The distribution of activated titanium dioxide crystals, wherein the size up to 1 nm is 0.3 vol%, the size up to 20 nm is 5-40 vol%, the size up to 80 nm is 10-80 vol%, the size up to 150 nm is 5-30 vol%, the size up to 250 nm is 5-20 vol%, the size greater than 250 nm is no more than 10 vol%, and, a distribution of activated silica particles, wherein 10-80% are of size 40-80 nm, 10-80% are of size 80-150 nm, less than 30% are of size 150-250 nm, and no more than 15% are of size greater than 250 nm, In the energy centers, ie in the quantum dot-local superheated zones, up to 80% of electronically excited triplet oxygen 3O 2 is present on the lattice surface, ensuring catalytic activity for the formation of active forms of oxygen in living organisms.

7. Use of a stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles produced according to claim 6 in a medicament and in combination with other active pharmaceutical ingredients, using the following therapeutically important amounts of the active substance of the crystals or particles: from 0.006 mg / ml for intravenous administration, from 0.01 mg / ml for intramuscular administration, from 0.01 mg / ml for oral administration, from 0.01 mg / ml for nasal administration, from 0.01 mg / ml for vaginal administration, from 0.01 mg / ml for rectal administration, from 0.01 mg / ml for topical ENT use, from 0.01 mg / ml for ocular use, and from 0.0003 mg / ml for topical application.

8. Use of the stable suspension of titanium dioxide heterocrystals and silicon dioxide particles as described in claim 6 as a catalyst, which converts oxygen from the triplet state 3O2 to the singlet state O2S1-3 at the expense of consuming thermal energy, the thermal energy including temperatures starting from 36.6°C in the human body and / or photon hyperthermia and / or waves and electromagnetic radiation, ensuring the energy required for converting oxygen from the triplet state to the singlet state, for synthesizing active forms of oxygen in the human body.

9. Use of the stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claim 6, characterized in that: In the presence of NAD+ enzymes of immune cells, targeted delivery of the stable suspension to the localized area of ​​inflammation is ensured in order to induce the formation of active forms of oxygen in inflammatory foci.

10. Use of the stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claim 6, characterized in that: Ensure the antiviral effect of the drug.

11. Use of the stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claim 6, characterized in that: Ensure the anti-pathogen and anti-viral effects of the agent.

12. Use of the stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claim 6, characterized in that: The adsorption capacity of crystals and particles in the pharmaceutical preparation ensures detoxification of the organism.

13. Use of the stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claim 6, characterized in that: It ensures that the insufficient oxidation processes in the living organism are eliminated in the pharmaceutical preparation.

14. Use of the stable suspension of titanium dioxide heterogeneous crystals and silicon dioxide particles according to claim 6, characterized in that: Ensures the induction of an immune response in vertebrates through physical or chemical interaction with an antigen.

Citation Information

Patent Citations

  • Nanoparticles for cancer sonodynamic and photodynamic therapy

    US20100262115A1

  • Nanoparticles of a heterocrystal mineral for use as a medicament and method of producing the same

    WO2007048634A2